Treatment of Proximal Femoral Fragility Fractures in Patients with COVID-19 During the SARS-CoV-2 Outbreak in Northern Italy. (17th June 2020) - Catellani, Francesco; Coscione, Andrea; D'Ambrosi, Riccardo; Usai, Luca; Roscitano, Claudio; Fiorentino, Gennaro
Abstract : Background: From February 20 to April 2020, the coronavirus SARS (severe acute respiratory syndrome)-CoV-2 spread in northern Italy, drastically challenging the care capacities of the national health care system. Unprepared for this emergency, hospitals have quickly reformulated paths of assistance in an effort to guarantee treatment for infected patients. Orthopaedic departments have been focused on elderly traumatology, especially the treatment of femoral neck fractures in patients with coronavirus disease-2019 (COVID-19). The purpose of the present study was to evaluate the orthopaedic management strategy for femoral fragility fractures in COVID-19-positive patients with the hypothesis that operative treatment may contribute to the overall stability of the patient. Methods: Sixteen patients affected by proximal femoral fracture and a recent history of fever, shortness of breath, and desaturation were admitted to the emergency room. Thoracic computed tomography (CT) and oropharyngeal swabs confirmed that they were positive for COVID-19, requiring hospitalization and prophylaxis with low-molecular-weight heparin. Results: Three patients died before surgery because of severe respiratory insufficiency and multiple-organ-failure syndrome. Ten patients underwent surgery on the day after admission, whereas 3 patients had suspended their use of direct thrombin inhibitors and needed surgery to be delayed until the third day after admission. In all patients except 1, we noted an improvement in terms of O2 saturation and assisted respiration. In 9 patients, hemodynamic and respiratory stability was observed at an average of 7 days postoperatively. Four patients who underwent surgical treatment died of respiratory failure on the first day after surgery (1 patient), the third day after surgery (2 patients), or the seventh day after surgery (1 patient). Conclusions: We noted a stabilization of respiratory parameters in 12 COVID-19-positive patients who underwent surgery treatment of proximal femoral fractures. We believe that in elderly patients with COVID-19 who have proximal femoral fractures, surgery may contribute to the overall stability of the patient, seated mobilization, improvement in physiological ventilation, and general patient comfort in bed. Level of Evidence: Prognostic Level IV . See Instructions for Authors for a complete description of levels of evidence.